Knowledge translation for realist reviews: a participatory approach for a review on scaling up complex interventions - Jennifer A. Boyko; Barbara L. Riley; Cameron D. Willis; Lisa Stockton; Dana Zummach; Jon Kerner; Kerry Robinson; Marie Chia (BMC, 2018)
Abstract Background Knowledge syntheses that use a realist methodology are gaining popularity. Yet, there are few reports in the literature that describe how results are summarised, shared and used. This paper aims to inform knowledge translation (KT) for realist reviews by describing the process of developing a KT strategy for a review on pathways for scaling up complex public health interventions. Methods The participatory approach used for the realist review was also used to develop the KT strategy. The approach included three main steps, namely (1) an international meeting focused on interpreting preliminary findings from the realist review and seeking input on KT activities; (2) a targeted literature review on KT for realist reviews; and (3) consultations with primary knowledge users of the review. Results The international meeting identified a general preference among knowledge users for findings from the review that are action oriented. A need was also identified for understanding how to tailor findings for specific knowledge user groups in relation to their needs. The literature review identified four papers that included brief descriptions of planned or actual KT activities for specific research studies; however, information was minimal on what KT activities or products work for whom, under what conditions and why. The consultations revealed that KT for realist reviews should consider the following: (1) activities closely aligned with the preferences of specific knowledge user groups; (2) key findings that are sensitive to factors within the knowledge user's context; and (3) actionable statements that can advance KT goals, activities or products. The KT strategy derived from the three activities includes a planning framework and tailored KT activities that address preferences of knowledge users for findings that are action oriented and context relevant. Conclusions This paper provides an example of a KT strategy for realist reviews that blends theoretical and practical insights. Evaluation of the strategy's implementation will provide useful insights on its effectiveness and potential for broader application.